1996
DOI: 10.1183/09031936.96.09051029
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological studies of the respiratory effects of air pollution

Abstract: Environmental epidemiological studies of the health effects of air pollution have been major contributors to the understanding of such effects. The chronic effects of atmospheric pollutants have been studied, but, except for the known respiratory effects of particulate matter (PM), they have not been studied conclusively. There are ongoing studies of the chronic effects of certain pollutant classes, such as ozone, acid rain, airborne toxics, and the chemical form of PM (including diesel exhaust).Acute effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 210 publications
2
59
0
4
Order By: Relevance
“…It appears from these studies that CAPS may be acting to alter lung antibacterial defense mechanisms important in the handling of ongoing pneumococcal infections. This scenario fits temporally with the epidemiologic data that indicate that deaths among exposed individuals occur relatively quickly following a PM episode, and that individuals with chronic respiratory disease were less likely than healthy individuals to recover from pulmonary infections following PM exposure (1,24,25).…”
Section: Discussionsupporting
confidence: 54%
“…It appears from these studies that CAPS may be acting to alter lung antibacterial defense mechanisms important in the handling of ongoing pneumococcal infections. This scenario fits temporally with the epidemiologic data that indicate that deaths among exposed individuals occur relatively quickly following a PM episode, and that individuals with chronic respiratory disease were less likely than healthy individuals to recover from pulmonary infections following PM exposure (1,24,25).…”
Section: Discussionsupporting
confidence: 54%
“…However, smoking might be considered as an effect modifier, although it is unclear whether smokers are more or less susceptible to the effects of air pollution than nonsmokers. It has been reported that smokers are less responsive than nonsmokers due to altered lung function and an increase in mucus, both of which could influence dose in the different regions of the lung [31]. It has also been suggested that smokers are more responsive than nonsmokers: in a study reported by DUSSELDORP et al [32], separate analyses in a small group of smokers (n=9) suggested a greater susceptibility of smokers to PM10 pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that exposure to fine particles is associated with tens of thousands of hospital admissions and premature deaths annually ( Dockery and Pope, 1994;Lebowitz, 1996;Lippmann and Thurston, 1996 ). These studies have demonstrated consistent associations, with coherence across various health endpoints (Bates, 1992 ).…”
Section: Introductionmentioning
confidence: 99%